Step-by-step explanation:

Answer:
y = 11
Step-by-step explanation:
8 × 2 + 5²- y = 2(y + 1) + 6
8 × 2 + 5²- y = 2y + 2 + 6
8 × 2 + 25 - y = 2y + 2 + 6
16 + 25 - y = 2y + 2 + 6
41 - y = 2y + 8
41 (- y + y) = (2y + y) + 8
41 = 3y + 8
41 - 8 = 3y (+ 8 - 8)
33 = 3y
33/3 = 3y/3
y = 11
There is three terms in the expression "n2+6n-3".
In Algebra a term is either a single number or variable, or numbers and variables multiplied together. Terms are separated by + or − signs, or sometimes by divide.
Answer:
It is known that 1 pint equals 16 ounces
Step-by-step explanation:
It is known that 1 pint equals 16 ounces. Then we use this data to transform a number of ounces into pints.
Suppose we have x ounces. We want to know how many pints are these x ounces. Then we perform the following operation

Where z pints is the amount equivalent to x ounces